Visualization Analysis of Sung Jin-Woo’s Character in Solo Leveling Comics - Dzakir, N A; Persada, S I P (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Sung Jin-Woo’s character, Solo Leveling Comics, is a web adaptation of a digital comic novel with an action fantasy genre created by comic artists named Chugong, H-goon and KI Soryeong. Solo Leveling was published in the form of a digital web novel, but as its popularity increased, Solo Leveling was adapted into a manhwa. Solo Leveling features a past storyline starting 10 years before the plot and the main character begins. At that time, there were random appearances of gates or portals all over the world. This gate represents a portal that connects the human world and the monster world. Explicitly the character Sung Jin-Woo displays illustrations of various scenes of violence such as beating various characters or stabbing other characters. This character visualization also seems to represent the characters of Sasuke and Naruto as one. The purpose of this study is to find out how to visualize the character Sung Jin-Woo in comics. The research method used in this study uses a descriptive-qualitative method of vehicle transfer analysis. Data sourced from literature studies. The results of this study show that there is a clear and varied development of the main character, namely Sung Jin-Woo, the comic artist provides narrative development to the main character in a clear and varied manner, by making variations, additions, simplifications, and subtractions that are influenced by the background of the storyline. without changing the main ideas and references.